Electroencephalogram in premature infants: from normal to pathological activity - D. A. Chegodaev; N. V. Pavlova; O. A. Lvova; L. V. Shalkevich (Русский журнал детской неврологии, 2019)
This study was aimed to assess electrophysiological brain activity in newborns of various gestational ages using electroencephalography (EEG). We summarized the data on the main EEG characteristics of premature infants and their dynamics and described the most common pathological EEG changes that can be identified at this age. We also discussed prognostic value of various neonatal EEG patterns (including their proportion and location), which allow verification of functional brain disorders at early stages.